Optimization of Minimarket Shopping Change Donation Management for the Development of Educational Programs - Sigit Hariyanto; Khusniati Rofi’ah; Ely Masykuroh (Journal of Economics, Law, and Humanities, 2026)
Background/Introduction: Shopping change donation programs as a form of Islamic philanthropy have significant potential to support educational development; however, their management optimization still requires strengthening in managerial aspects and program sustainability. Research Objectives: Objectives: This study aims to analyze the management of the consumer shopping change donation program at Surya Mart, Ponorogo Regency, its management optimization, and the impact of donation distribution on the development of educational programs. Methodology: This study employed a descriptive qualitative approach with a field research design. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data collection, classification, reduction, and conclusion drawing. Data validity was tested through source triangulation involving Surya Mart, LAZISMU Ponorogo, and the Muhammadiyah Primary and Secondary Education Council of Ponorogo. Results: The findings indicate that the donation management program has implemented modern management principles through planning, organizing, implementation, and supervision functions. Management optimization was strengthened through the application of Management by Process (MBP) by implementing fundraising strategies and improving donor services, which contributed to a significant increase in donation amounts each year. The distribution of donations for educational development also fulfilled the indicators of benefit, suitability, sustainability, and program impact. Unique Contribution: This study offers a Management by Process (MBP)-based optimization model for shopping change donation management in supporting educational development programs through collaboration between minimarkets and Islamic philanthropic institutions. Conclusion: The management of Surya Mart shopping change donations has proven effective in increasing fundraising and supporting sustainable educational development through modern management principles and MBP. Recommendations: Future research is recommended to explore digital-based retail donation management and expand the study to other minimarket networks to develop a more comprehensive donation management model.